Simulation and Analysis of a Static Synchronous Series Compensator for Power System Stability Enhancement with Fuzzy Controller - Kumar, B.Likhith; Rao, B.Hanumatha (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The Flexible A.C Transmission systems devices [FACTS] play an important role in the efficient operation of the complex power system utilities. With the energy storage systems they have a good control over the real and reactive power compensation and also improve the transient stability for a quality power system. A Static Synchronous Series Compensator [SSSC] is a series connected converter based on FACTS control which can provide a series reactive power compensation for a transmission system. The design of controller for the SSSC system is examined in this study. In this paper a Proportional integral [PI] controller and extended fuzzy controller is compared with the SSSC for a two connected generating system. A Fuzzy logic controller is designed for the efficient operation of the power system with SSSC integrated with energy storage device. The Proportional integral and FUZZY logic controllers are analyzed with the MATLAB/SIMULINK software